Representasi Pengajian Online Dalam Meningkatkan Kecerdasan Spiritual Remaja Muslimah - Mudrik Minanurohman; Salsabila Febrianti Nurfadhilah; Syarifah Setiana Ardiati (THORIQOTUNA: Jurnal Pendidikan Islam, 2024)
Recitation is a group or congregation that has a desire to increase religious knowledge, through non-formal education with various activities or activities organized by a group of people as a form of religious value development. The purpose of this study is to determine the level of spiritual intelligence of Muslim adolescents before and after being given the implementation of Online Study activities and the effect of the implementation of Online Study activities in increasing the spiritual intelligence of Muslim adolescents in Dusun. Cibonteng Village. Tanjungmulya The research method used by the author is an experimental method with the type of Pre-Experimental Design (One-Group Pretest-Posttest design) where this experimental research is carried out on only one group selected randomly without any comparison group to then be given an initial test or pre-test before being given treatment and given a final test or post-test after treatment, this study uses a quantitative approach. The results of the study and data analysis showed that the spiritual intelligence of Muslim adolescents before being given treatment was in the low category with an average score of 59.3 and after being given treatment the average score became 66.6 and was included in the high category. This shows that the implementation of Online Religious Studies activities can increase the spiritual intelligence of Muslim adolescents